2015
DOI: 10.1051/0004-6361/201423954
|View full text |Cite
|
Sign up to set email alerts
|

Scaling properties of a complete X-ray selected galaxy group sample

Abstract: Context. Upcoming X-ray surveys like eROSITA require precise calibration between X-ray observables and mass down to the lowmass regime to set tight constraints on the fundamental cosmological parameters. Since an individual mass measurement is only possible for relatively few objects, it is crucial to have reliable and clearly understood scaling relations that relate the total mass to easily observable quantities. Aims. The main goal of this work is to constrain the galaxy group scaling relations corrected for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

68
329
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 246 publications
(399 citation statements)
references
References 71 publications
(176 reference statements)
68
329
2
Order By: Relevance
“…Eckmiller et al (2011) show that there is a good agreement between clusters and groups for most scaling relations, albeit with increased intrinsic scatter on the group regime, which is not totally unexpected due to the complicated baryonic physics at play in low-mass systems. Recent results by Lovisari et al (2014), however, argue that while the observed scaling relations for galaxy groups are in agreement with those obtained for galaxy clusters, the scaling relation obtained after corrections for selection effects are consistent with a gradual steepening towards the low-mass regime.…”
Section: Introductionsupporting
confidence: 67%
See 1 more Smart Citation
“…Eckmiller et al (2011) show that there is a good agreement between clusters and groups for most scaling relations, albeit with increased intrinsic scatter on the group regime, which is not totally unexpected due to the complicated baryonic physics at play in low-mass systems. Recent results by Lovisari et al (2014), however, argue that while the observed scaling relations for galaxy groups are in agreement with those obtained for galaxy clusters, the scaling relation obtained after corrections for selection effects are consistent with a gradual steepening towards the low-mass regime.…”
Section: Introductionsupporting
confidence: 67%
“…It is an effect that has been shown to affect scaling relations, namely resulting in higher observed normalisations as compared to the actual normalisations in scaling relations for clusters (e.g. Ikebe et al 2002;Stanek et al 2006;Pratt et al 2009;Mantz et al 2010;Lovisari et al 2014). In this sample, we have applied an additional luminosity cut which could further contribute to the bias.…”
Section: Bias Correctionmentioning
confidence: 99%
“…The temperature profile and the cooling time of 21.6±4.41 Gyr determined by Lovisari et al (2015), and the temperature map by Bogdán et al (2011), indicate that Abell 194 does not harbor a cool core.…”
Section: X-ray Propertiesmentioning
confidence: 83%
“…Also, comparing the measured X-ray flux of the Comet with those of small galaxy groups using the L − T relation from Lovisari et al (2015), we conclude a redshift range z = 0.036 +0.021 −0.012 , which also excludes this structure from being a background cluster.…”
Section: The "Comet"mentioning
confidence: 82%
“…The solar abundances are set to the values given by Asplund et al (2009). The influence of the abundance table, especially at lower plasma temperatures on the best-fit parameters, are shown, e.g., in Lovisari et al (2015). (Fasano et al 2006) in green.…”
Section: Data Analysis and Resultsmentioning
confidence: 99%